Anti-Breast Cancer Potency of Multistage Extraction from Jamur Dewa (Agaricus blazei Murill) Solvents on MCF-7 Cells - Misgiati Misgiati; Sukardiman Sukardiman; Aty Widyawaruyanti (Indonesian Journal of Cancer Chemoprevention, 2017)
ABM (Agaricus blazei Murill) is a basidiomycetes fungus. ABM is used by people for the treatment of diabetes, antihypertention, anticholesterol, anticancer, and immunostimulant. ABM contains terpene, steroids, agaritine, vitamin C, vitamin E, and betaglucane. In this research, ABM extract was tested as an anti-breast cancer in vitro using MCF-7 breast cancer cells. The extract was obtained from the multistage extraction process of several solvents in turn, the solvent used, among others, n-hexane, dichloromethane (DCM), chloroform, ethyl acetate, butanol, and water. The results of the research were the obtained IC50 value from n-hexane extract 247,17 μg /ml; extract DCM 227μg/ml ; chloroform extract 215,64 μg /ml ; extract of ethyl acetate 234,9 μg/ml ; butanol extract 500,78 μg/ml; while the water extract was inactive. Based on these results can be considered for further research to fractionate in order to know which class compounds have the potency as anticancer within the extracts.Key words : Agaricus blazei, multistage extraction, MCF-7 cells.